The role of the inter-municipal cooperation for the development of the territories (Путеводитель предпринимателя)
The retrospective review on practical experience of the inter-municipal cooperation given in the article let summarize and synthesize the basic directions and forms of cooperation of parties of integration processes; determine factors which restrain the development of inter-municipal cooperation; define perspective forms of inter-municipal cooperation for assuring sustainable social-economic development of the territory.